Local networks and the internet : From Protocols to Interconnection - Toutain, Laurent; Minaburo, Ana. (London : ISTE ; Hoboken, NJ : Wiley, 2011)
"This title covers the most frequently used elements of the Internet and Intranet and their development. It details the latest developments in research and covers new themes such as IP6, MPLS, and IS-IS routing, as well as explaining the function of standardization committees such as IETF, IEEE, and UIT. The book is punctuated with numerous examples and applications which will help the reader to place protocols in their proper context"--
Introduction -- Standardization and wiring -- Ethernet and IEEE 802.3 protocols -- The LLC and SNAP sublayers -- Interconnection by bridges: the spanning tree algorithm -- Internet -- IP protocols -- Level 4 protocols: TCP, UDP and SCTP -- Address resolution and automatic configuration protocols -- Routing protocols -- Internal routing protocols -- External routing protocols -- Virtual local networks -- MPLS (Multi Protocol Label Switching) -- IP on point-to-point links: PPP -- Network administration -- Security -- Flow management -- Bibliography -- Index.
Includes bibliographical references (pages 679-680).
Includes bibliographical references and index.
Print version record.
Keywords: Intranets (Computer networks); Internet; Computer network protocols; Intranets (Computer networks); Local area networks (Computer networks); Internet; Computer network protocols; TECHNOLOGY & ENGINEERING -- Telecommunications; TECHNOLOGY & ENGINEERING -- Telecommunications; COMPUTERS -- Networking -- Network Protocols; Computer network protocols; Internet; Intranets (Computer networks); Intranets (Computer networks); Local area networks (Computer networks); Internet; Computer network protocols; Electronic books